5 year oncological outcomes of the HIGHLOW randomized clinical trial. Issue 3 (March 2023) - Mari, Giulio; Santambrogio, Gaia; Crippa, Jacopo; Cirocchi, Roberto; Origi, Matteo; Achilli, Pietro; Ferrari, Giovanni; Megna, Stefano; Desio, Matteo; Cocozza, Eugenio; Maggioni, Dario; Montroni, Isacco; et al.
Abstract: Introduction: The oncological outcomes of low ligation (LL) compared to high ligation (HL) of the inferior mesenteric artery (IMA) during low-anterior rectal resection (LAR) with total mesorectal excision are still debated. The aim of this study is to report the 5 year oncologic outcomes of patients undergoing laparoscopic LAR with either HL vs. LL of the IMA Materials and methods: Between June 2014 and December 2016, patients who underwent elective laparoscopic LAR + TME in 6 Italian non-academic hospitals were randomized to HL or LL of IMA after meeting the inclusion criteria (HighLow trial; ClinicalTrials.gov Identifier NCT02153801). We analyzed the rate of local recurrence, distant metastasis, overall survival, disease-specific survival, and disease-free survival at 5 years of patients previously enrolled. Results: Five-year follow up data were available for 196 patients. Recurrence happened in 42 (21.4%) of patients. There was no statistically significant difference in the distant recurrence rate (15.8% HL vs . 18.9% LL; P = 0.970) and pelvic recurrence rate (4, 9% HL vs 3, 2% LL; P = 0.843). No statistically significant difference was found in 5-year OS (p = 0.545), DSS (p = 0.732) or DFS (p = 0.985) between HL and LL. Low vs medium and upper rectum site of tumor, conversion rate, Clavien-Dindo post-operative grade ≥3 complications and tumor stage were found statistically significantly associated to poor oncological outcomes in univariate analysis; in multivariate analysis, however, only conversion rate and stage 3 cancer were found to be independent risk factors for poor DFS at 5 years. Conclusion: We confirmed the results found in the previous 3-year survival analysis, the level of inferior mesenteric artery ligation does not affect OS, DSS and DFS at 5-year follow-up. Highlights : Oncological outcomes do not differ according to the level of vascular ligation in rectal resection for cancer. Cancer stage and conversion rate are associated with poor oncological outcomes in rectal cancer Low IMA ligation does not affect survival in laparoscopic TME since the level of the vascular ligation is not one of the risk factors for local or distant disease recurrence